2004
DOI: 10.1038/sj.onc.1207871
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of ICAM-1 and VCAM-1 expression in endothelial cells treated by photodynamic therapy

Abstract: Photodynamic therapy (PDT) is a treatment for cancer and several noncancerous proliferating cell diseases that depends on the uptake of a photosensitizing compound followed by selective irradiation with visible light. In the presence of oxygen, irradiation leads to the production of reactive oxygen species (ROS). A large production of ROS induces the death of cancer cells by apoptosis or necrosis. A small ROS production can activate various cellular pathways. Here, we show that PDT by pyropheophorbide-a methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 38 publications
(43 reference statements)
2
35
0
1
Order By: Relevance
“…Here we extend these findings to show that bradykinin, through TRPM7, induces expression of proinflammatory molecules VCAM-1 and COX-2, which are known downstream targets of calpain (24,37,45). Previous studies showed that bradykinin influences inflammatory mediators and cellular adhesion molecules (35).…”
Section: Discussionmentioning
confidence: 55%
“…Here we extend these findings to show that bradykinin, through TRPM7, induces expression of proinflammatory molecules VCAM-1 and COX-2, which are known downstream targets of calpain (24,37,45). Previous studies showed that bradykinin influences inflammatory mediators and cellular adhesion molecules (35).…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, the elevation of VCAM-1 expression only at mRNA level also suggests a potential for synergism. The discrepancy between mRNA and protein levels of VCAM-1 is not unknown [44,45]. MicroRNAs may block translation of VCAM-1 without degradation of mRNA or post-translational degradation can decrease the protein level, however, the exploration of the molecular mechanism is beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitative PCR cDNA was prepared in a 20 ml final volume with 1 mg RNA as described (Volanti et al, 2004). cDNA (2 ml) was mixed with 10 ml SYBR Green Mix (Applied Biosystems, Warrington, UK) and forward and reverse primers for each gene of interest, or with 300 nM forward (5 0 -GAGTATGCCTGCCGTGTG-3 0 ) and 300 nM reverse (5 0 -AATCCAAATGCGGCATCT-3 0 ) b2-microglobulin (B2M) primers in a 20 ml final volume.…”
Section: Analysis Of Microarraysmentioning
confidence: 99%